Evaluation of Various Treatment Outcomes in Tempromandibular Disorder - Dalaei MJ (Tehran University of Medical Sciences, 1999)
Numerous techniques are used for treatment of tempromandibular disorder (TMD). Two aims should be considered when managing patients with TMD."na) pain reduction, feeling of improvement, prevention of untoward sequel of TMD."nb) Complete cure and enabling the patients to continue a normal life as much as possible. For an exact and successful treatment the following certain rules should be followed:"n1} The physician's competence and knowledge in anatomy, physiology, psychology of the disorder."n2) Pay attention to patient's statement and being sympathetic, developing rapport, performing a complete and careful clinical examination."n3) Considering the patient's psychological or physiological deficits."n4) Eliminating TMD Precipitating factor."nIn general, treatment of this disease like other disease of bones and muscles should not be addressed aggressively such as"nsurgery or occlusion therapy. Simple and conservative methods should be applied for treating this disorder, as some cases"nare self-limiting and require no intervention.